Psychological correlates of COVID-19 pandemic in the Austrian population - Claudia Traunmüller; Rene Stefitz; Kerstin Gaisbachgrabner; Andreas Schwerdtfeger (BMC, 2020)
Abstract Background COVID-19 poses the greatest challenge for the entire world since the Second World War. Governments are forced to define strict measures to avoid the spreading of the virus, which may further impose psychological burden for the majority of the population. The aim of this study was to evaluate the psychological distress in Austria during the initial stage of the COVID-19 outbreak. Methods From 25 March to 3 April 2020, an anonymous online survey was conducted. Target group included all members of the Austrian population older than 16 years. The survey addressed the following areas (1) and sociodemographic data, (2) physical and mental health; (3) knowledge and concerns about COVID-19; (4) contact with infected people; (5) prevention efforts; (6) need for further information. The Impact of Event Scale-Revised (IES-R) and the Depression, Anxiety and Stress Scale (DASS-21) were used to assess mental health. Analyses were based on 4126 individuals (74% female, age: M = 38.68, SD = 13.36). Results 43.3% rated the psychological impact as moderate (5.6%) or severe (37.7%). 26.5% reported moderate (13.3%) to severe (13.2%) depression; 20.3% moderate (8.9%) to severe (11.4%) anxiety and 21.2% reported to suffer from moderate (10.5%) or severe stress (10.7%). Being female, higher age, lower levels of education, concern about family members, internet as main source of information, student or pupil status, poor self-rated health, and downplaying the seriousness of the problem were significantly associated with higher psychological burden. Protective factors were the possibility to work in home office, frequent (indirect) contact with family or friends, the availability of virus-specific information, confidence in the diagnosis capability, and physical activity during the crisis. Conclusion This study is among the first in Europe on the psychological correlates of the COVID-19 pandemic. 37.7% of the Austrian study population reported a severe psychological impact on the event and 1 in 10 is considered to suffer from severe depression, anxiety or stress. The present findings inform about the identification of protective factors, psychologically vulnerable groups and may guide the development of psychological interventions.